2003
DOI: 10.1021/ma021307g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Stereoregular AABB-Type Polyamides from Carbohydrate-based Monomers Having d-manno and l-ido Configurations

Abstract: Polycondensation of 1,6-diamino-1,6-dideoxy-2,3,4,5-tetra-O-methyl-D-mannitol or 1,6-diamino-1,6-dideoxy-2,3,4,5-tetra-O-methyl-L-iditol with aromatic and aliphatic dicarboxylic acids has been used to prepare a series of regio-and stereoregular AABB-type polyamides. We also describe the preparation of 1,6-diamino-1,6-dideoxy-3,4-O-isopropylidene-D-mannitol and 1,6-diamino-1,6-dideoxy-2,5-di-O-methyl-3,4-O-isopropylidene-D-mannitol and their polycondensation reactions with the same dicarboxylic acids. The obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…There were two methods of polycondensation of dicarboxylic acid chloride with diamine: solution polycondensation and interfacial polycondersation. Owing to the rapid hydrolysis of the aliphatic dicarboxylic acid dichloride and premature precipitation of the polymers, high‐viscosity polyamides were rarely obtained using the interfacial polycondensation method,9 and therefore, the solution polycondensation method was used to prepare polyamides in this work (Scheme ). The structures of the obtained polyamides were verified by FTIR, 1 H‐NMR, and 13 C‐NMR spectroscopies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were two methods of polycondensation of dicarboxylic acid chloride with diamine: solution polycondensation and interfacial polycondersation. Owing to the rapid hydrolysis of the aliphatic dicarboxylic acid dichloride and premature precipitation of the polymers, high‐viscosity polyamides were rarely obtained using the interfacial polycondensation method,9 and therefore, the solution polycondensation method was used to prepare polyamides in this work (Scheme ). The structures of the obtained polyamides were verified by FTIR, 1 H‐NMR, and 13 C‐NMR spectroscopies.…”
Section: Resultsmentioning
confidence: 99%
“…When compared with Refs. 9 and 16, solution polycondensation of di‐ O ‐methyl‐ L ‐tartaryl chloride with diamines to prepare optically active polyamides does not need activation of the diamines and is characterized with shorter reaction time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that these can be transformed into water-soluble polyacids upon saponification of ester side groups. PAs derived from carbohydrates are the object of current attention, because they are not only optically active, but also for its potential as biodegradable and biocompatible materials [72][73][74][75][76][77]. Mallakpour and coworkers [78][79][80] have investigated the synthesis of PAs from the polycondensation reaction of chiral 5-(4-methyl-2-phthalimidylpentanoylamino)isophthalic acid, (2S)-5-(3-phenyl-2-phthalimidylpro-panoylamino)iso-phthalic acid and 5-(3-methyl-2-phthalimidylpentanoylamino) isophthalic acid with several aromatic and aliphatic diisocyanates such as 4,4!-diphenylmethane diisocyanate (MDI), toluylene-2,4-diisocyanate (TDI), isophorone diisocyanate (IPDI) and hexamethylene diisocyanate (HDI) under microwave irradiation as well as conventional technique (Figure 2).…”
Section: Synthetic Optically Active Condensation Polymers 21 Polyammentioning
confidence: 99%
“…In recent years, sustained efforts have been devoted to rendering polyamides more degradable, to extend their applications to new fields demanding materials with lower environmental impact or displaying biodegradable and biocompatible properties (2).…”
Section: Introductionmentioning
confidence: 99%